THE EFFECT OF WHOLE SEED (Barringtonia racemosa) WATER EXTRACT ON ERYTHROCYTE, HEMOGLOBIN AND HEMATOCRITE COUNT OF WHITE RAT (Rattus norvegicus) EXPOSED TO CIGARETTE SMOKE - Dasrul, D; Aliya, Yayang Nuri Al; Sutriana, Amalia; Asmilia, Nuzul; Daud, Razali (Universitas Syiah Kuala, 2023)
This study aims to determine the effect of Barringtonia racemosa seed extract on the number of erythrocytes, hemoglobin levels, and the percentage of hematocrit in white rats (Rattus norvegicus) exposed to cigarette smoke. A total of 25 white rats Wistar strain, aged 3-4 months, male, weighing 180-200 g, were randomly divided into 5 treatment groups, each group consisting of 5 rats. Positive control group (KP) without exposure to cigarette smoke and without administration of Barringtonia racemosa seed extract, negative control group (KN) exposed to cigarette smoke without administration of Barringtonia racemosa seed extract. Treatment groups P1, P2, P3 were exposed to cigarette smoke and given Barringtonia racemosa seeds with doses of 50, 100, and 150 mg/kg BW/day, respectively. The extract was administered orally for 30 days. Blood collection in all groups was carried out via the orbital vein using a hematocrit pipette after the rats had been sedated with 0.2 mL of ketamine. Erythrocyte, hemoglobin, and hematocrit values were calculated using a hematology analyzer. Data were analyzed using one-way pattern analysis of variance (ANOVA). The results showed that giving Barringtonia racemosa seeds at doses of 50, 100 and 150 mg/kg/day had a significant effect (P0.05) in increasing the values of erythrocytes, hemoglobin, and hematocrit of white rats exposed to cigarette smoke compared to the control group which was not given the extract. In conclusion, the administration of Barringtonia racemosa seed extract can increase the number of erythrocytes, hemoglobin levels, and the percentage of hematocrit exposed to cigarette smoke.